Exploring the Relationships Among Innovation, Collaboration, and School Change in a Mixed Methods - Walker, Aneta Hogan (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2018)
Continuous school improvement efforts require schools to prepare, organize, and lead change. This study examined how a school created a context for change by implementing an innovation to improve teaching practices, school culture, and student learning outcomes. Implementing innovation requires school leaders to understand the process of change to successfully sustain school improvement efforts. The purpose of this research study was to assess the effectiveness that an innovative hybrid schedule had on improving student learning outcomes and school culture. This mixed-method research study used data generated by the AdvancEds Stakeholder Feedback Survey, the ACT Aspire Student Achievement Tests, and teacher interviews. The analysis of this studys data indicated several factors that facilitated change through the implementation of the innovative hybrid schedule. The researcher discovered these overall factors related to the benefits of students changing classes, teachers becoming content specialists, collaboration through PLCs and vertical planning. Additionally, the results revealed that significant change occurred in school culture based on the AdvancEds Stakeholder Feedback Survey. Additionally, student learning outcomes measured by ACT Aspire Reading and Mathematics Student Achievement Tests showed a statistically significant improvement in both reading and math.